BENTUK PENYAJIAN MUSIK IRINGAN TARI NGAJAT LESUNG DI DESA SELUAS KECAMATAN SELUAS KABUPATEN BENGKAYANG - Surina Yunita; Ismunandar Ismunandar; Chiristianly Silaban (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe background of this research wasdescribe the form of accompaniment music of Ngajat Lesung dance in Seluas village, Seluas sub-district Bengkayang regency. The problem of this research were how was the form ofaccompaniment music of Ngajat Lesung dance in Seluas village Seluas sub-district Bengkayang regency, how to desaign the implementation of research results the form ofaccompaniment musicof Ngajat Lesung dance in Seluas village Seluas sub-district Bengkayang regency in the world of educatioan. The method used in this research was descriptive method with qualitative form and uses an ethnomusicology approach. The source of data in this research wasKarsono, Utandi, and Simon. The data in this research were obtained through the interview, observation, and documentation result about the form accompaniment music Ngajat Lesung dance. The data collectingtechniques in this research were the form of observation, interview, and documentation techniques.Validity check of data in the form of extention of observation and triangulation. The result of this research were music instrument, player, stage arrangement, makeup, fashion, sound arrangement, lighting arrangement, formation, and the order of performance. The result of this research can be implemented in learning art and culture, junior high school level in the 2013 curiculum. Keywords:Dayak community in Bengkayang regency, Ngajat Lesung, The form ofaccompaniment music.